Quality of Marriages of Husband-Wife Families Working in the Formal Sector During the Covid-19 Pandemic as well as Work-Family Conflicts and Family Interactions That Occur: Quality of Marriages of Husband-Wife Families Working in the Formal Sector During the Covid-19 Pandemic as well as Work-Family Conflicts and Family Interactions That Occur - Deshila A. Dyoga; Tin Herawati; Defina (Journal of Family Sciences, 2022)
The COVID-19 that has occurred has changed all human routines. COVID-19 has also prompted countries to issue work from home (WFH) policies. With this policy, the line between office work and homework is invisible. This condition triggers conflict, especially between husband and wife working, namely between work and family. However, good interaction between family members can be a mediator for working couples. In this regard, the study aims to analyze family interactions and the effect of work-family conflict on the quality of marriage for husband and wife working families during the COVID-19 pandemic. The design of this research is a cross-sectional study and was carried out in the city of Bogor in March 2021. Research respondents are wives who work in the formal sector and have school-age children, and the number is 65 families. The method in this study was self-administered, and an online questionnaire was used. Analysis of the influence of family characteristics, work-family conflict, and family interaction on marriage quality used regression test. As a result, during the COVID-19 pandemic, marriage quality was in the high category, with work-family conflict in the low category and family interactions were in the moderate category. Based on the regression test results, it is known that the quality of marriage is positively and significantly influenced by the length of the marriage and negatively significantly by work-family conflict. The research implication is that work-family conflicts can be overcome with good interactions between family members during the pandemic.